ANALYSIS OF ZAKAT, INFAQ AND SHADAQAH MANAGEMENT METHODS IN THE FRAMEWORK OF MICRO BUSINESS DEVELOPMENT IN THE INDONESIAN ZAKAT INITIATIVE (IZI) BENGKULU REPRESENTATIVE - Peliyani Sistika; Amir Mukadar; Kurniawan Saprihadi (Journal of Islamic, Social, Economics and Development, 2023)
This research is a qualitative research, which aims to find out the management of zakat, infaq, and shadaqah funds at LASNAZ Zakat Initiative (IZI) Bengkulu Representative, strategies for improving the management of zakat, infaq, and shadaqah in developing micro-enterprises, and how the benefits of zakat funds are channeled to mustahik for development of micro-enterprises in economic welfare. The objects of this research are the Head of the Indonesian Zakat Initiative (IZI) Bengkulu Representative, the Head of the Zakat Empowerment Utilization Sector, the Head of the Zakat Education and Partnership Sector, as well as several mustahik micro business actors receiving zakat. The results of this study can be concluded that the management of zakat, infak, and shadaqah funds at the Indonesian Zakat Initiative (IZI) collects funds from muzakki through services provided by IZI such as zakat pickup services, bank accounts, zakat pedia, IZI Point. The strategy carried out by the Indonesian Zakat Initiative (IZI) in increasing the development of micro-enterprises is verifying mustahik are entitled to receive funds in the form of carts and business capital, to increase income. This program is called lapak Berkah.